The distribution systems for organic farming produce in Poland and Spain – similarities and differences - Kacprzak, Ewa; Maćkiewicz, Barbara (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
At the turn of the 21st century, European countries experienced a dynamic growth of interest in organic farming and the development of distribution systems for organic farming produce. This article is an attempt to assess the development of the distribution systems for organic farming produce in Spain and Poland and to identify the key drivers determining the systems. A hypothesis has been adopted that, despite different conditions, the systems operate in a similar way in both countries (though various distribution channels have different significance), and that they are becoming more and more similar to the distribution systems for conventional farming produce. New trends in the development of Polish and Spanish distribution channels for organic farming produce have also been identified.